Prediction of Alzheimer’s Disease-Associated Genes by Integration of GWAS Summary Data and Expression Data - Hao, Sicheng; Wang, Rui; Zhang, Yu; Zhan, Hui (Frontiers in Genetics, 2019)
Alzheimer's disease (AD) is the most common cause of dementia. It is the fifth leading cause of death among elderly people. With high genetic heritability (79%), finding the disease's causal genes is a crucial step in finding a treatment for AD. Following the International Genomics of Alzheimer's Project (IGAP), many disease-associated genes have been identified; however, we do not have enough knowledge about how those disease-associated genes affect gene expression and disease-related pathways. We integrated GWAS summary data from IGAP and five different expression-level data by using the TWAS method and identified 15 disease-causal genes under strict multiple testing (alpha < 0.05), and four genes are newly identified. We identified an additional 29 potential disease-causal genes under a false discovery rate (alpha < 0.05), and 21 of them are newly identified. Many genes we identified are also associated with an autoimmune disorder.